Metabolomic and Physiological Changes in Fagus sylvatica Seedlings Infected with Phytophthora plurivora and the A1 and A2 Mating Types of P. ×cambivora - Corcobado, Tamara; Milenković, Ivan; Saiz-Fernández, Iñigo; Kudláček, Tomáš; Plichta, Roman; Májek, Tomáš; Bačová, Aneta; Ďatková, Henrieta; Dálya, László Benedek; Trifković, Miloš; Mureddu, Davide; Račko, Vladimír; et al. (Journal of fungi (Basel, Switzerland), 2022)
Phytophthora infections are followed by histological alterations, physiological and metabolomic adjustments in the host but very few studies contemplate these changes simultaneously. Fagus sylvatica seedlings were inoculated with A1 and A2 mating types of the heterothallic P. ×cambivora and with the homothallic P. plurivora to identify plant physiological and metabolomic changes accompanying microscope observations of the colonization process one, two and three weeks after inoculation. Phytophthora plurivora-infected plants died at a faster pace than those inoculated with P. ×cambivora and showed higher mortality than P. ×cambivora A1-infected plants. Phytophthora ×cambivora A1 and A2 caused similar progression and total rate of mortality. Most differences in the physiological parameters between inoculated and non-inoculated plants were detected two weeks after inoculation. Alterations in primary and secondary metabolites in roots and leaves were demonstrated for all the inoculated plants two and three weeks after inoculation. The results indicate that P. plurivora is more aggressive to Fagus sylvatica seedlings than both mating types of P. ×cambivora while P. ×cambivora A1 showed a slower infection mode than P. ×cambivora A2 and led to minor plant metabolomic adjustments.
Keywords: sugars; photosynthesis; root pathogens; gas exchange; proline; GABA; mortality; spectral reflectance; chlorophyll fluorescence